Upconversion‐Nanoparticle‐Assisted Radical Polymerization at λ=974 nm and the Generation of Acidic Cations. Issue 11 (21st September 2017) - Chen, Zhijun; Oprych, Dennis; Xie, Chaoming; Kutahya, Ceren; Wu, Si; Strehmel, Bernd
Abstract: Upconversion nanoparticles (UCNPs) sensitised photolytic cleavage of the blue/UV photoinitiator bis(4‐methoxybenzoyl) diethyl germanium (1 ).1 initiated radical photopolymerisation in combination with NaYF4 :TmYb@NaYF4 UCNPs. A λ =974 nm near‐infrared (NIR) laser served as the excitation source to generate blue and UV light. In addition, a metal‐free photo‐ATRP system (ATRP=atom transfer radical polymerisation), composed of iso ‐propyl thioxanthone (ITX), N, N, N′, N′′, N′′ ‐pentamethyldiethylenetriamine (PMDETA) and α‐bromo( iso ‐butyl) ethylester (α‐BrBuEt) was used instead of1 . This resulted in a significant smaller polydispersity compared to the UCNP/1 system. Control of polymerization was successfully demonstrated by means of a chain extension experiment showing control of chain termination. For the first time, we demonstrated photolytic formation of acidic cations in such NIR UCNP systems composed of an ITX/iodonium photoinitiator for the sensitized generation of acidic cations. In addition, 1 also resulted in crosslinking of 1, 6‐hexanediol diacrylate (HDDA) in combination with UCNPs and NIR laser excitation. UV filter materials such as TiO2 do not significantly interfere with crosslinking. Abstract : Let′s get the ball rolling : Upconversion nanoparticles (NaYF4 :TmYb@NaYF4 UCNPs) sensitize the photolytic formation of radicals and acidic cations resulting in radical polymerization and crosslinking. UV‐light‐absorbing additives do not interfere with formation of the polymer.